CONVECTIVE HEAT TRANSFER IN CYCLONE DEVICE WITH EXTERNAL GAS RECIRCULATION - S. V. Karpov; A. A. Zagoskin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The article considers the convective heat transfer on the surface of a hollow cylinder or several billets in a cyclone device with the new principle of external gas recirculation. According to this principle, transport of coolant from the lateral surface of the chamber, where the temperature is the highest, in the axial region is being fulfilled due to the pressure drop between the wall and axial areas of cyclonic flow. Dependency analysis of average and local heat transfer coefficients from operational and geometrical parameters has been performed; the generalized similarity equations for the calculation of the latter have been suggested. It is demonstrated that in case of download of a cyclone chamber with several billets, the use of the considered scheme of the external recirculation due to the specific characteristics of aerodynamics practically does not lead to noticeable changes in the intensity of convective heat transfer. Both experimental data and the numerical simulation results obtained with the use of OpenFOAM platform were used in the work. The investigations fulfilled will expand the area of the use of cyclone heating devices.